JOQARÍ OQÍW ORÍNLARÍNDA TALABALARDA MILLETLERARALÍQ QARÍM-QATNAS MÁDENIYATÍN RAWAJLANDÍRÍWDÍŃ KONCEPTUAL MODELINIŃ NÁTIYJELILIGI - Bekbergenov, A.A. (SCIENCE and SOCIETY, 2025)
The article demonstrates all components of the model for developing students' interethnic communication culture, their interrelationships, the purpose of forming students' communicative culture, its psychological and didactic content, and the specific methods, tools, and forms of encouragement and organization. This also refers to the logical relationships between the psychological and didactic content of pedagogical practice.
Keywords: model; student; education; upbringing; pedagogy; psychology; communicative culture; component; ethics; humanity; personality